THE ROLE OF SIPD APPLICATION IN INCREASING TRANSPARENCY AND BUREAUCRACY IN DELI SERDANG REGENCY GOVERNMENT - Sianturi, Jeklin Monalisa (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The transparency of bureaucracy in local government is crucial in ensuring good governance and accountability. This study explores the role of the Regional Government Information System (SIPD) in promoting bureaucratic transparency in Deli Serdang Regency. The SIPD platform, introduced by Indonesia’s Ministry of Home Affairs, aims to digitalize public administration processes, particularly in budgeting, planning, and reporting. This qualitative descriptive research collected data through interviews with civil servants, direct observation, and document analysis. The findings show that SIPD contributes to better information openness, reduces the potential for corruption, and enhances efficiency in public service. However, several obstacles such as limited human resources capacity and digital infrastructure issues were identified. The study recommends strengthening digital literacy and developing sustainable policies to improve the effectiveness of SIPD implementation.